The hobo transposable element of Drosophila can be cross-mobilized in houseflies and excises like the Ac element of maize. - Atkinson, P W (1993)
The hobo transposable element from Drosophila melanogaster was found to be capable of excision, resulting in donor sites unlike those reported for any other transposable element currently known in animals. These empty sites most closely resemble those left by the transposable elements Ac and Tam3 in Zea mays and Antirrhinum majus, respectively. Like Ac and Tam3, the hobo element was found to function in a distantly related species, in this case the housefly Musca domestica. Hobo excision in M. domestica was found not to require the expression of hobo-encoded transposase but instead appears to be driven by an endogenous hobo transposase-like activity. DNA sequences displaying high homology to the hobo transposase gene were isolated from the genome of M. domestica and appear to be part of a mobile-element system related to hobo, Ac, and Tam3.